Adoption of water conservation technologies among smallholder farmers in Osun State, Nigeria - Oluremi, Aminu, Folasade; Farouq, Morakinyo, Akinwumi; Abd’Malik, Suleiman, (International Journal of Sustainable Agricultural Research, 2025)
Water scarcity and inefficient water management practices pose significant threats to agricultural productivity and rural livelihoods in Nigeria, particularly among smallholder farmers who rely heavily on rain-fed agriculture. Despite increasing awareness of water conservation technologies (WCTs) as viable strategies for sustainable agricultural water use, their adoption among farmers remains relatively low and uneven across regions, highlighting the need to understand factors influencing smallholder farmers’ adoption of water conservation technologies in Osun State, Nigeria. The study focused on identifying the WCTs embraced by farmers, understanding their motivations for adoption, and analyzing the factors influencing their adoption decisions. Data was collected via a pre-tested questionnaire administered to 120 smallholder farmers selected through a multistage sampling process. Descriptive statistics and a multivariate probit (MVP) model were employed for data analysis. Findings indicated that the majority (55.8%) of farmers were male, aged 41-50, with primary education (41.7%), and household and farm sizes averaging 6 persons and 4 hectares, respectively. The most adopted WCTs included irrigation/dam (68.3%), grass strips (62.5%), stone bund (50%), soil bund (41.7%), and contour ploughing (32.5%). Reasons for adoption ranged from yield increase to flood control and soil fertility improvement. The MVP model revealed several factors influencing adoption, including farmers' demographics, education, farming experience, land acquisition methods, and access to credit and extension services. The study suggests enhancing educational opportunities, credit access, farmer associations, and extension services as essential policy measures to foster technology adoption in the study area.